Um estudo bibliográfico sobre a utilização de mapas conceituais como ferramenta de avaliação da aprendizagem: algumas considerações no ensino de física - Costa, Rosilaine Gomes de Santana (2013)
This work is a bibliographical research, which is a systematic review without meta-analysis, performed in various national and international journals and proceedings in the International Conferences on Concept Maps (CM) aiming to analyze how the researches which make use of CM are being developed as an assessment tool to of student learning and it also establishes criteria to evaluatethem. The goal in using CM is to check students learning process regarding to the contents learned in the classroom, getting information about the concepts learned significantly, as well as those who have not been learned or learned incorrectly, making sure that these same students were able to establish connections between the new concepts and the already existing knowledge in their cognitive structure. It was observed through the analysis of the methodology of the researched articles, that there is a significant number of works, from a universe of 105, making use of CM as an assessment tool in different areas, including Physics, and with different methodologies. It was also noticeable a certain concern from the authors in establishing criteria to check/assess whether CM prepared by students achieved the desired goals. It is hoped that this research can guide teachers/researchers who intend to work with such an tool of learning assessment, which, although greatly important to education, is not widely used in the educational environment